PENGEMBANGAN BISNIS BERBAHAN DASAR PANDAN DI WILAYAH PERBATASAN MELALUI PENDEKATAN ONE VILLAGE ONE PRODUCT DENGAN POLA KLASTER - Dedy; Angela Siokalang, Maria; Daniel (Management and Sustainable Development Journal, 2024)
Sajingan Besar is one of the areas in the border area that has abundant natural resource potential, one of which is pandan leaves. This research aims to provide a business development model to improve the welfare of the surrounding community. The approach used in this study uses a qualitative approach with a descriptive analysis method. The data source is primary data through field observation, interviews and documentation. The findings in this study state that in the development of natural resources in Sajingan Besar which is dominated by pandanus-based artisans, it can be developed with the One Village One Product (OVOP) approach with a cluster pattern. Pandanus-based handicrafts can be directed to become superior products in the Sajingan Besar area. The concept of One Village One Product (OVOP) is one of the approaches that can be used in designing a model for managing economic potential in the region with the goal of allowing the region to develop one superior product.